Formalización del personal de consorcio D&E SAC y el pago de su Impuesto a la Renta-Personas Jurídicas periodo 2011. - Holguín García, Carlos (2011)
The general objective of this research was to know in what extent does the formalization of the CONSORCIO D & E SAC staff in the payment of Income Tax for Corporations 2011.This because it was intended to demonstrate that the Tax income-Corporations period 2011 would have been reduced if it had formalized the staff of the company. We have investigated the dimensions or characteristics of the formalization of the company staff and the annual income tax paid in the period 2011 using surveys of 17 workers of the company, a list of matching observation and documental analysis, calculations were also performed to delineate the real costs and sundries of the staff and the subsequent effect it had for Income Tax for Corporations 2011. As a result of the investigation, it was proved that the company only declared to the National Superintendency of Tax Administration (SUNAT) the 12.65% of all costs and sundries of its staff in 2011, which influenced to have a balance to stabilize Income Tax-Corporations of S/.11 003 in the period 2011. This is because the company failed to pay social benefits to workers, or deducted contributions to the pension system and avoided much of Essalud payment, it means the staff was not formalized. For these reasons, it was concluded that if the company had formalized its staff, the Income Tax for Corporations period 2011 should been reduced so much, that instead of paying S /. 11 003, would have had a favorable balance of S /. 168 971 to compensate it in the coming years.